Mechanical behavior of patched steel panels at elevated temperatures - Surendran, S; Manjunath, G L; Lee, S K (Sustainable Marine Structures, 2019)
Preventive maintenance is an accepted practice in engineering to keep the structural reliability of ship hulls at the highest possible level. Designers ensure a longer period in between the consecutive maintenance of ship hull parts to optimize expenditure. This is relevant in view of the difficulty in reaching farthest corners in ballast tanks, fuel storage tanks, cofferdams etc. Prior maintenance of the deck and hull parts save a considerable amount of the owner’s budget.A portable technology like patching becomes more handy and economic. Performance of both unpatched and patched samples during dynamic loading conditions being examined in the present investigation. The high strength steel panels with a dimension of 70mm×15mm×3mm were edge cracked for lengths of 4mm and 7mm, with width of 1mm for both. The edge cracked high strength steel panels are repaired with composite patches using GFRP (glass fiber reinforced plastic), CFRP (carbon fiber reinforced plastic) and AFRP (aramid fiber reinforced plastic). The patching was done by 3 and 5 layered and impact tested by Charpy impact tester at ranges of high temperatures. The amount of energy absorbed in the impact is converted to dynamic fracture toughness values and compared for evaluating the performance of FRP (fiber reinforced plastics). Finite element analysis was done for evaluating the stress intensity factors at different types of patching and testing conditions. Comparatively the AFRP patched samples showed better dynamic fracture toughness values at different temperatures. ER